2011
DOI: 10.2903/j.efsa.2011.2186
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the Pest Risk Analysis onPhytophthora ramorumprepared by the FP6 project RAPRA

Abstract: The Panel on Plant Health was asked to deliver a scientific opinion on the Pest Risk Analysis on Phytophthora ramorum prepared by the FP6 project RAPRA, taking into account comments by Member States and additional information since RAPRA. P. ramorum is the oomycete causing sudden oak death in the USA and leaf and twig blight/dieback on a range of ornamental species in North America and Europe. Currently P. ramorum is not listed as a harmful organism in Council Directive 2000/29/EC, but the Commission adopted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 139 publications
(263 reference statements)
0
6
0
Order By: Relevance
“…A study on A1-A2 progeny revealed a high incidence of non-Mendelian inheritance and of aneuploidy suggestive of significant differences in synteny (gene arrangements), and possibly in chromosomal number, between lineages (119). Nonetheless, two studies have determined that a percentage of oospores generated from laboratory crosses may be viable (5,35), highlighting the importance of avoiding intermixing of lineages carrying different mating types (Fig. 1).…”
Section: P Ramorum: An Unusually Complex Forest Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on A1-A2 progeny revealed a high incidence of non-Mendelian inheritance and of aneuploidy suggestive of significant differences in synteny (gene arrangements), and possibly in chromosomal number, between lineages (119). Nonetheless, two studies have determined that a percentage of oospores generated from laboratory crosses may be viable (5,35), highlighting the importance of avoiding intermixing of lineages carrying different mating types (Fig. 1).…”
Section: P Ramorum: An Unusually Complex Forest Pathogenmentioning
confidence: 99%
“…ramorum highlights the indirect effects of human commercial and industrial activities on natural ecosystems: in this case, a pandemic affecting forest trees has been clearly driven by the longdistance trade of infected ornamental plants used not for reforestation but for landscaping in the urban-wild interface. Given this scenario, it should be no surprise that in less than a decade, P. ramorum has driven a significant policy shift in how plant pathogens are diagnosed by the regulatory agencies of many countries, moving from a diagnosis exclusively dependent on morphological identification of cultures to a more articulated process in which culturing, immunological, and nucleotide sequence-based detection assays must be utilized (2,35).…”
mentioning
confidence: 99%
“…One possible pathway of entry for P. ramorum according to Sundheim et al. ( 2009 ), EFSA PLH Panel ( 2011 ) and Thomsen et al. ( 2023 ) is susceptible wood.…”
Section: The Pests Highlighted By the European Commissionmentioning
confidence: 99%
“…Possible pathways of entry for Phytophthora ramorum are plants for planting (excluding seed and fruit) of known susceptible hosts; plants for planting (excluding seed and fruit) of non-host plant species accompanied by contaminated attached growing media; soil/growing medium (with organic matter) as a commodity; soil as a contaminant; foliage or cut branches; susceptible (isolated) bark and susceptible wood (EFSA PLH Panel, 2011).…”
Section: Biologymentioning
confidence: 99%